TEI, Ontologies, Linked Open Data: Geolat and Beyond - Fabio Ciotti; Maurizio Lana; Francesca Tomasi (Journal of the Text Encoding Initiative)
This paper presents the rationales and the logical architecture of Geolat — Geography for Latin Literature, a project for the enrichment of Latin literature which makes use of a complex mix of TEI markup, Semantic Web technologies and formal ontologies. The purpose of Geolat is the annotation of the geographical and personal references in a corpus of Latin TEI encoded texts. These annotations are linked to a set of ontologies that give them formal semantics, and can finally be exposed the as linked open data, in order to improve the documents’ interoperability with other existing LOD and to enhance information retrieval possibilities. The paper is organized as follows: first we introduce the project in order to explain the steps needed to complete it (section 2); then we describe the ontological modeling and the TEI encoding in Geolat, by focusing on both places and persons (section 3). We then discuss the annotation data model (section 4). In conclusion, we introduce some future directions (section 5).